Nano-TiCl4.SiO2: A Versatile and Efficient Catalyst for Synthesis of 14-aryl or alkyl-14H-dibenzo[a,j]xanthenes - B. F. Mirjalili; A. Bamoniri; L. Zamani (Journal of Nanostructures, 2013)
Nano-silica supported titanium tetrachloride (TiCl4.SiO2) was prepared and used as an acid catalyst for the 14-aryl or alkyl-14H-dibenzo[a,,j]xanthenesreaction under solvent-free conditions. Compared to the classical 14-aryl or alkyl-14H-dibenzo[a,j]xanthenesreaction conditions, this method consistently has the advantage of excellent yields, mild reaction conditions, ease of workup, survival of different functional groups and short reaction times.